A bio-inspired nano-material recapitulating the composition, ultra-structure, and function of the glycosaminoglycan-rich extracellular matrix of nucleus pulposus. (February 2023) - Yang, Xing-Xing; Yip, Chi-Hung; Zhao, Shirui; Ho, Yi-Ping; Chan, Barbara Pui
Abstract: The nucleus pulposus (NP) of intervertebral disc represents a soft gel consisting of glycosaminoglycans (GAGs)-rich extracellular matrix (ECM). Significant loss of GAGs and normal functions are the most prevalent changes in degenerated disc. Attempts targeted to incorporate GAGs into collagen fibrous matrices have been made but the efficiency is very low, and the resulting structures showed no similarity with native NP. Inspired by the characteristic composition and structures of the ECM of native NP, here, we hypothesize that by chemically modifying the collagen (Col) and hyaluronic acid (HA) and co-precipitating with GAGs, a bio-inspired nano-material recapitulating the composition, ultra-structure and function of the GAG-rich ECM will be fabricated. Compositionally, the bio-inspired nano-material namely Aminated Collagen-Aminated Hyaluronic Acid-GAG (aCol-aHA-GAG) shows a record high GAG/hydroxyproline ratio up to 39.1:1 in a controllable manner, out-performing that of the native NP. Ultra-structurally, the nano-material recapitulates the characteristic 'nano-beads' (25 nm) and 'bottle-brushes' (133 nm) features as those found in native NP. Functionally, the nano-material supports the viability and maintains the morphological and phenotypic markers of bovine NP cells, and shows comparable mechanical properties of native NP. This work contributes to the development of a compositionally, structurally, and functionally biomimetic nano-material for NP tissue engineering.